Barry Faulkner papers - Faulkner, Barry, 1881-1966.
Chiefly correspondence (1900-1966) with family associates. Also includes typescripts of articles and speeches and photographs of Faulkner's murals. Correspondents include Witter Bynner, Eric Gugler, Leon Kroll, James Johnson Sweeney, and Lawrence Grant White.
In part, photocopies and typescripts.
Artist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Art; Mural painting and decoration, American; Bynner, Witter, -- 1881-1968 -- Correspondence; Gugler, Eric, -- 1889-1974 -- Correspondence; Kroll, Leon, -- 1884-1974 -- Correspondence; Sweeney, James Johnson, -- 1900-1986 -- Correspondence; White, Lawrence Grant -- Correspondence; Artists